Mental Health and Bullying in the United States Among Children Aged 6 to 17 Years. (March 2015) - Turcotte Benedict, Frances; Vivier, Patrick M.; Gjelsvik, Annie
This article examines the association between mental health disorders and being identified as a bully among children between the ages of 6 and 17 years. Data from the 2007 National Survey of Children's Health were examined. A total of 63, 997 children had data for both parental reported mental health and bullying status. Bivariate analysis and logistic regression was performed to assess the association between mental health status and being identified as a bully with an age-stratified analysis and sub-analysis by type of mental health disorder. In 2007, 15.2% of U.S. children ages 6 to 17 years were identified as bullies by their parent or guardian. Children with a diagnosis of depression, anxiety, or depression had a threefold increased odds of being a bully. The diagnosis of depression is associated with a 3.31 increased odds (95% CI = [2.7, 4.07]) of being identified as a bully. Children with anxiety and attention deficit and hyperactivity disorder (ADHD) had similar odds. The diagnosis of a mental health disorder is strongly associated with being identified as a bully. In particular, depression, anxiety, and ADHD are strongly associated with being identified as a bully. These findings emphasize the importance of providing psychological support to not only victims of bullying but bullies as well. Understanding the risk profile of childhood bullies is essential in gaining a better grasp of this public health problem and in creating useful and appropriate resources and interventions to decrease bullying.